Human tyrosinase is able to oxidize both enantiomers of rhododendrol. (3rd September 2014) - Ito, Shosuke; Gerwat, Wolfram; Kolbe, Ludger; Yamashita, Toshiharu; Ojika, Makoto; Wakamatsu, Kazumasa
Summary Racemic RS‐4‐(4‐hydroxyphenyl)‐2‐butanol (rhododendrol, RD) was used as a topical skin‐whitening agent until it was recently reported to induce leukoderma. We then showed that oxidation of RD with mushroom tyrosinase rapidly produces RD‐quinone, which is quickly converted to RD‐cyclic quinone and RD‐hydroxy‐p‐quinone. In this study, we examined whether either or both of the enantiomers of RD can be oxidized by human tyrosinase. Using a chiral HPLC column, racemic RD was resolved optically to R(−)‐RD and S(+)‐RD enantiomers. In the presence of a catalytic amount of l‐dopa, human tyrosinase, which can oxidize l‐tyrosine but not d‐tyrosine, was found to oxidize both R(−)‐ and S(+)‐RD to give RD‐catechol and its oxidation products. S(+)‐RD was more effectively oxidized than l‐tyrosine, while R(−)‐RD was less effective. These results support the notion that the melanocyte toxicity of RD depends on its tyrosinase‐catalyzed conversion to toxic quinones and the concomitant production of reactive oxygen species.